(untitled) (Research Journal, 2023)
As the field of language teaching has been influenced by different methods and approaches developed over time, the pedagogy journey has been shifted from method-based teaching to post-method pedagogy. This article critically examines the same pedagogical shift from method-based model to post-method pedagogy that the ELT situation at present is in a transitional period regarding language teaching applying the beliefs and principles of both PPP (i.e., presentation, practice, and production) model and PPP (i.e., particularity, practicality, and possibility) pedagogy. The beliefs, principles, features, and criticisms published in different books and journals at different times are major sources of information for this article. The critical examination of those ideas in connection with my own teaching-learning experience showed that the pedagogical shift from method-based teaching to post-method pedagogy is a turning point in language teaching because the method-based model prescribes teaching procedures without considering the contextual, practical, and political factors and issues, whereas post-method pedagogy gives primary emphasis on those contextual factors and local issues. Thus, psychological, contextual, glocal, socio-economic/political, and research-based teaching and learning perspectives have been discussed as the major themes of this article.